The phenomenon of spinsterhood in contemporary Iraqi theater discourse (Al-Academy, 2023)
The basic units that form the convergence of the systems of the dramatic image of women are units based on the mentality of the entire society and what it stores within its collective idea of a general composition about women and their issues and all the phenomena that affect their general formation, as the form and style in dealing with women’s issues developed through the stages of the development of art and theater From inception to our time now, the follower of the global theatrical path finds a different image of women in terms of dramatic formation and the general topic around which the event revolves. Studying and highlighting women’s phenomena and proposing ways to treat them were among the most important goals of many international or Arab playwrights The Iraqi theater, like other theaters, came to present and treat women’s issues, including the phenomenon of spinsterhood, how to treat and limit it, and shed light on all the reasons and causes that made this phenomenon spread recently among girls, especially Arab and Iraqi women in general. Towards the writers and directors of the Iraqi theater who dealt with this phenomenon in a dramatic manner directly. A play came and they lived a happy life written by Ali Abd al-Nabi al-Zaidi and directed by Kazem Nassar. And conclusions about the study of this phenomenon, especially in the Iraqi theater.